Social-ecological Resilience of a Nuosu Community-linked Watershed, Southwest Sichuan, China - Urgenson, Lauren S.; Hagmann, R. Keala; Henck, Amanda C.; Harrell, Stevan; Hinckley, Thomas M.; Shepler, Sara Jo; Grub, Barbara L.; Chi, Philip M. (Ecology and society, 2010)
Farmers of the Nuosu Yi ethnic group in the Upper Baiwu watershed report reductions in the availability of local forest resources. A team of interdisciplinary scientists worked in partnership with this community to assess the type and extent of social-ecological change in the watershed and to identify key drivers of those changes. Here, we combine a framework for institutional analysis with resilience concepts to assess system dynamics and interactions among resource users, resources, and institutions over the past century. The current state of this system reflects a legacy of past responses to institutional disturbances initiated at the larger, national system scale. Beginning with the Communist Revolution in 1957 and continuing through the next two decades, centralized forest regulations imposed a mismatch between the scale of management and the scale of the ecological processes being managed. A newly implemented forest property rights policy is shifting greater control over the management of forest resources to individuals in rural communities. Collective forest users will be allowed to manage commodity forests for profit through the transfer of long-term leases to private contractors. Villagers are seeking guidance on how to develop sustainable and resilient forest management practices under the new policy, a responsibility returned to them after half a century and with less abundant and fewer natural resources, a larger and aggregated population, and greater influence from external forces. We assess the watershed’s current state in light of the past and identify future opportunities to strengthen local institutions for governance of forest resources.